Pengembangan Buku Ajar Pendidikan Kewarganegaraan Berbasis Pendidikan Multikultural Bermuatan Gerakan PPK di SDN 082 Bengkulu Utara - Wulandari, Beti Yuniana (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This study aims to develop a multicultural education-based textbook containing PPK in Citizenship Education learning. This research is a development research with the Research and Development (RnD) method. The population in this study were sixth-grade students at SD Negeri 082 Bengkulu Utara. The sample of this study was 5 sixth-grade students of SDN 082 Bengkulu Utara. The research instruments were interview guidelines, validation questionnaires, and student responses. Based on the results of the textbook validation test from three textbook experts, it was declared feasible. Based on the results of the student response questionnaire, the final percentage was 84.88% with the criteria of being suitable for use. It was concluded that the illustrated storybook based on Multicultural Education containing PPK developed by researchers was suitable for use as a companion textbook for learning Citizenship Education content in sixth-grade SDN 082 Bengkulu Utara.